2015
DOI: 10.1007/s10198-015-0679-8
|View full text |Cite
|
Sign up to set email alerts
|

A cost-utility analysis of ingenol mebutate gel for the treatment of actinic keratosis: a Scottish perspective

Abstract: Ingenol mebutate gel is a cost-effective therapy for the first-line treatment of AK from a Scottish NHS perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Pharmacoeconomic calculations (e.g. 29,44,45 ) using either standard gamble or TTO methodology resulted in utilities of 0.99 and 0.98. 46,47 However, these two studies included a total number of 25 patients and were not specific for AK but for a broad variety of dermatological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacoeconomic calculations (e.g. 29,44,45 ) using either standard gamble or TTO methodology resulted in utilities of 0.99 and 0.98. 46,47 However, these two studies included a total number of 25 patients and were not specific for AK but for a broad variety of dermatological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in their recent structured review on PROMs, authors from the United Kingdom expressed the need to analyse NMSC QL using a common standardised instrument and recommended the implementation of EQ‐5D in this disease spectrum . The EQ Index in particular represents a very robust outcome measure that can also be implemented in the calculation of quality‐adjusted life years (QALYs) in future health economic evaluations of NMSC treatments …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase 3 studies showed its efficiency in clearing AK, with sustained clearance over 12 months, using concentrations of 0.015% for face and scalp and 0.05% for trunk and extremities [111]. There is evidence to suggest that IM has higher efficacy than diclofenac 3% and IMQ 5% in the treatment of AK [120].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported the efficacy of the topically applied gel in the field therapy of AKs and its effect on the clearance of both clinically evident and subclinical lesions [10,12,31,35]. In a long-term follow-up study, Garbe et al [36] reported a persisting clinical clearance in 50% of the patients after 12 months.…”
Section: Discussionmentioning
confidence: 99%